EFEITOS DE CARVACROL E TIMOL, LIVRES OU EM COMBINAÇÃO COM CIPERMETRINA, SOBRE O CARRAPATO Rhipicephalus microplus. - TAVARES, Caio Pavão (2022)
The cattle tick, Rhipicephalus microplus, is an ectoparasite of great economic importance in livestock. The occurrence and spread of this tick are mainly controlled using synthetic acaricides. However, this control method is associated with several problems, including the selection of multiresistant populations. New acaricide compounds, including products of natural origin, must be characterized. The monoterpenes, carvacrol and thymol, present themselves as a potential alternative acaricide, both isolated and combined with other molecules; however, the mechanism of action of these monoterpenes, as well as the mechanisms involved in the synergistic effect of these compounds, need to be better elucidated in ticks. The present study aims to evaluate the efficacy and potential mode of action of the combination of cypermethrin and thymol in ticks from two populations with different levels of susceptibility to cypermethrin (low and high susceptibility), as well to evaluate the effects of carvacrol and thymol on the antioxidant and detoxifying enzymes of larvae from the same populations. The determination of the acaricide activity of cypermethrin and thymol in larvae was performed at different concentrations. The engorged females were divided into five experimental groups (n = 20): 1) Untreated control group; 2) Control group: 2.0% (v/v) DMSO; 3) Thymol group: 1300 μg/mL thymol; 4) Cypermethrin Group: 3700 μg/mL of cypermethrin; 5) Combination of cypermethrin (3700 μg/mL) + thymol (1300 μg/mL). A subgroup was used to determine the control percentage and another subgroup, with ten adults from each treatment, was used to quantify thymol and cypermethrin by HPLC chromatographic analysis. Carvacrol and thymol were tested at concentrations ranging from 0.14 to 5.0 mg∙mL-1 in both populations to determine LC1, LC25, LC50, and LC75. Larvae of both populations of R. microplus were treated with four letal concentrations of each monoterpene to determine the activity of the enzymes, glutathione-S-transferase (GST), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPX). All compounds tested were effective on larvae from both populations, and the combination with thymol decreased the LC50 of cypermethrin (232.4 to 52.7 μg/mL) on the low-susceptibility population. The combination of thymol and cypermethrin was also effective in engorged females, with a higher control percentage than the group of ticks treated with cypermethrin alone. From HPLC analyzes, a higher concentration of cypermethrin (pop. 1: 30.3 ± 6.9 and pop. 2: 45.4 ± 17.7 ng/mg) was detected in the tissues of engorged females treated with the combination compared to analyte concentrations in groups treated with cypermethrin only (pop. 1: 12.4 ± 4.4 pop. 2: 25.5 ± 9.4 ng/mg). R. microplus larvae from the Jaguar population treated with different lethal concentrations of carvacrol and thymol displayed a dose-dependent increase in CAT, GPX, SOD, and GST after treatment with LC25. Further, larvae treated with the LC75 had the highest levels of enzyme activity for carvacrol (1.76 mg·mL-1) and thymol (1.32 mg·mL-1). CAT, GPX, SOD, and GST activity in Porto Alegre strain larvae treated with carvacrol and thymol also increased significantly up to the LC50 of each monoterpene. However, at the LC75 of carvacrol and thymol, a decrease in the activity of all enzymes was observed. According to the results obtained in this thesis, we demonstrated for the first time the acaricide effect of the combination of thymol + cypermethrin in R. microplus, and that the presence of thymol increases the concentration of cypermethrin in the internal tissues of engorged females through a possible mechanism for increase the penetration of cypermethrin at the cuticular level. Likewise, we demonstrated for the first time the effect of carvacrol and thymol on important antioxidant and detoxifying enzymes in the tick R. microplus.